A Novel Intelligent Shore-to-Ship Power Supply System Using Collaborative Motor Control - Pan, Lin; Shao, Jingkai (Frontiers in Mechanical Engineering, 2020)
In this paper, a novel type of intelligent cable lifting device for shore-to-ship power connection system is proposed. By analyzing the shortcomings of the commonly used lifting methods in inland port, the structure and control circuit of the new cable lifting device are designed based on motor collaborative control. The reliability and effectiveness of the proposed control strategy are verified by establishing the mathematical model of the motor and Simulink software simulation analysis. The cable lifting device can adjust the cable delivery position in inland port. At the same time, it can significantly reduce manual operation and improve the efficiency of shore-to-ship power connection operation.